Negócio jurídico e a incidência tributária - Pinho, João Ricardo Dias de (2016)
We strive, in this thesis, to the study of juridical business in the tax incidence context. In addition, we had as background the tax planning theme. In a way that, juridical business topics, analyzed throughout the work, are those which matter the most to tax incidence, as considered from a survey with the judged of the Tax Revenue Management Board CARF, regarding the unlawfulness of tax planning. We used as premises some lessons from semantic constructivism-logical theory, speech acts, intentionality and macro action